2017
DOI: 10.1111/idh.12295
|View full text |Cite
|
Sign up to set email alerts
|

Oral cancer screening practices of Canadian dental hygienists

Abstract: Dental hygienists in this study are regularly conducting OCSs; however, they lack comfort discussing sensitive topics such as transmission of oral HPV, and screenings may not be fully comprehensive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
3
14
0
1
Order By: Relevance
“…Most recently, a 2017 study by Clarke et al on oral cancer screening practices of Canadian dental hygienists concluded that dental hygienists with a bachelor's degree felt more prepared to conduct screenings than those dental hygienists practising with a diploma …”
Section: Discussionmentioning
confidence: 99%
“…Most recently, a 2017 study by Clarke et al on oral cancer screening practices of Canadian dental hygienists concluded that dental hygienists with a bachelor's degree felt more prepared to conduct screenings than those dental hygienists practising with a diploma …”
Section: Discussionmentioning
confidence: 99%
“…Likewise, dentists' attitudes and skills regarding oral cancer practices are crucial in their engaging in such behaviors [20,33,34]. Results of the present study are in line with previously-published findings in relation to dentists' limited performance of full clinical oral cancer examinations and educating patients on risk factors relating to oral cancer [19,20,35]. If the faculty members do not perform full clinical oral cancer examinations and educate patients about its related risk factors, these kinds of behavior can be transmitted to their dental students [36].…”
Section: Discussionsupporting
confidence: 89%
“…Further, it was evident in a meta-synthesis that patients with late detection of oral cancer are more likely to be in an advanced stage of oral cancer [34]. Behavioral factors, such as the lack of oral cancer examinations, the lack of patient education about oral cancer as well as oral cancer self-examination, and delaying seeking out medical care were also found to be associated with oral cancer late detection [35].…”
Section: Early Versus Late Detection Of Oral Cancermentioning
confidence: 99%
“…Knowledge levels about HPV and HPV-OPC prevention have been positively associated with communication with patients about HPV and sexually transmitted infections (STIs) among dental hygienists (Daley et al, 2018), and has been studied among dentists as well (Vázquez-Otero et al, 2018). Comfort in communicating to patients about HPV may be associated with educational level and gender in the dentist and dental hygienist professions (Vázquez-Otero et al, 2018; Poelman et al, 2018; Clarke et al, 2018). However, increased knowledge about HPV topics could address communication deficits and self-efficacy (Daley et al, 2011).…”
Section: Introductionmentioning
confidence: 99%